Correction: Ma et al. Rad52 Oligomeric N-Terminal Domain Stabilizes Rad51 Nucleoprotein Filaments and Contributes to Their Protection against Srs2. Cells 2021, 10, 1467 - Emilie Ma (MDPI AG, 2021)
The authors wish to make the following changes to their paper [...]